Effect of Sugar Composition and Drying Time on Tomato Taste - Maradona, Maradona; Hujjatusnaini, Noor; Swestyani, Sondra (BIODIK, 2024)
Habaring Hurung Subdistrict, located in the Bukit Batu district of Palangka Raya City, is one of the tomato suppliers for the capital region, with a production range of 2,336 to 2,481. Fully ripe tomatoes tend to spoil quickly, with a relatively short storage life of 3-4 days. One of the ways tomatoes are utilized is by processing them into date tomatoes, a sweet snack made from tomatoes that are processed to resemble dates in taste and shape. This is done to enhance the appeal of tomato processing to the community. The research design used in this study is a Randomized Block Design, with the variables being tested as sugar composition and drying time, based on the preference level of date tomatoes. The preference level of date tomatoes was evaluated using hedonic tests, specifically focusing on taste. The panelists involved in the preference evaluation were 15 individuals from the general public and students. Data analysis was conducted using Duncan's Multivariate Range Test (DMRT). The results of the hedonic tests showed that sugar compositions of 600-800 grams, in terms of color, taste, and texture, were highly preferred (â‰¤ 80%) by the panelists, but the effect was not statistically significant. On the other hand, drying times of 3-6 days, in terms of color, taste, and texture, were highly preferred (â‰¥ 60%) and had a significant impact.